Hydraulic conductivity in layered saturated soils assessed through a novel physical model (2018)
This paper introduces a novel physical model for measuring the hydraulic conductivity of granular materials in saturated conditions. An innovation in the location of the device’s piezometers allows the device to be used to assess the permeability of layered soils for both parallel and perpendicular flows. The model’s square section construction makes soil compaction easy. Design methodology took issues of construction, calibration and implementation into account. Permeability coefficients in directions parallel and perpendicular to soil stratification were measured, and Student’s t-test was performed for the relation of experimental results and existing numerical correlations. Analysis of the results shows that the physical model can replicate seepage in layered soils with parallel and perpendicular flows as occurs in field. Furthermore, it was found that it is possible to validate the experimental calibration data by use of statistical techniques.